CIMA - C02 Fundamentals of Financial Accounting: Revision Kit - BPP Learning Media (BPP Learning Media, 2012)
The most important factor in passing any assessment is plenty of question practice. The questions in the C2 Practice and Revision Kit cover all areas of the syllabus and are in the same order as the Text chapters. They include separate banks of multiple-choice questions (MCQs) and objective-test questions. All are of assessment standard. Therefore students can tailor their question practice to concentrate on areas of weakness, such as basic bookkeeping or incomplete records, or dip into topics as they revise them. There are also two mock assessments to test the whole syllabus.